Neighbourhood choice and neighbourhood reproduction - Bergström, Lina (Institute for the Study of Labor, 2014)
Although we know a lot about why households choose certain dwellings, we know relatively little about the mechanisms behind neighbourhood choice. Most studies of neighbourhood choice only focus on one or two dimensions of neighbourhoods: typically poverty and ethnicity. This paper argues that neighbourhoods have multiple dimensions and that models of neighbourhood choice should take these dimensions into account. We propose the use of a conditional logit model. From this approach we can gain insight into the interaction between individual and neighbourhood characteristics which lead to the choice of a particular neighbourhood over alternative destinations. We use Swedish register data to model neighbourhood choice for all households which moved to a neighbourhood in the city of Uppsala between 1997 and 2006. Our results show that neighbourhood sorting is a highly structured process where households are very likely to choose neighbourhoods where the neighbourhood population matches their own characteristics.